Replication of Nonautonomous Retroelements in Soybean Appears to Be Both Recent and Common1[W][OA] - Wawrzynski, Adam; Ashfield, Tom; Chen, Nicolas W G; Mammadov, Jafar; Nguyen, Ashley; Podicheti, Ram; Cannon, Steven B; Thareau, Vincent; Ameline-Torregrosa, Carine; Cannon, Ethalinda; Chacko, Ben; Couloux, Arnaud; et al. (Plant physiology (Bethesda), 2008)
Retrotransposons and their remnants often constitute more than 50% of higher plant genomes. Although extensively studied in monocot crops such as maize (Zea mays) and rice (Oryza sativa), the impact of retrotransposons on dicot crop genomes is not well documented. Here, we present an analysis of retrotransposons in soybean (Glycine max). Analysis of approximately 3.7 megabases (Mb) of genomic sequence, including 0.87 Mb of pericentromeric sequence, uncovered 45 intact long terminal repeat (LTR)-retrotransposons. The ratio of intact elements to solo LTRs was 8:1, one of the highest reported to date in plants, suggesting that removal of retrotransposons by homologous recombination between LTRs is occurring more slowly in soybean than in previously characterized plant species. Analysis of paired LTR sequences uncovered a low frequency of deletions relative to base substitutions, indicating that removal of retrotransposon sequences by illegitimate recombination is also operating more slowly. Significantly, we identified three subfamilies of nonautonomous elements that have replicated in the recent past, suggesting that retrotransposition can be catalyzed in trans by autonomous elements elsewhere in the genome. Analysis of 1.6 Mb of sequence from Glycine tomentella, a wild perennial relative of soybean, uncovered 23 intact retroelements, two of which had accumulated no mutations in their LTRs, indicating very recent insertion. A similar pattern was found in 0.94 Mb of sequence from Phaseolus vulgaris (common bean). Thus, autonomous and nonautonomous retrotransposons appear to be both abundant and active in Glycine and Phaseolus. The impact of nonautonomous retrotransposon replication on genome size appears to be much greater than previously appreciated.